Aspectos a considerar para una buena gestión en los almacenes de las empresas (Centros de Distribución, CEDIS) - Arrieta Posada, Juan Gregorio (2011)
In this document we present different aspects that are necessary to perform an excellent administration and control of distribution centers that corporations may have. If these ideas are implemented correctly in an efficient way, most of the productivity problems in the warehouse could be solved easily. Thus, it is important to evaluate the products’ activity profile, the layout of the warehouse and the products’ flow through the distribution center. The objective of this process is to obtain the conditions of a world class warehouse.